The Methods and Learning Design of English for Specific Purpose for Aircraft Maintenance Engineering Subject in Aviation English - Meita Maharani Sukma; Laila Rochmawati; Fatmawati Fatmawati (Jurnal Penelitian)
This research discusses about English for specific purposes in particular integration of the methods and learning design in aircraft maintenance engineering subject for cadets in Aviation Polytechnic of Surabaya. Aviation Polytechnic of Surabaya has some specific curricullum of each study programs. The curriculum depends on the major of each study programs. The researchers concern for aircraft maintenance engineering study program in aviation english subject to be researched. The researchers interested to explain the vocabulary subject in Aviation English by deviding into 4 groups, this research offers an example passage of how this can be done and evaluated the passage. Requirements analysis is made and the curriculum is presented on the teaching of vocabulary subject in Aviation English using observation and comparison methods, so the cadets can get and learn the aircraft engineering subject in theory and practice effectively in the classroom and apply it in the world of work. The results of this research is to analyze the progress of the cadets skill using these designs or methods by practicing and exploring their knowledge, we can see the table result of each group in this paper. The cadets can learn many vocabularies and understand the curriculum design of aircraft maintenance engineering subject in Aviation English and organize the material for learning that is appropriate to current conditions.